My Lady Nicotine: A Study in Smoke - Barrie, J. M. (James Matthew), 1860-1937; Prendergast, Maurice, 1858-1924 (Salt Lake City, UT : Project Gutenberg, 2006)
"My Lady Nicotine: A Study in Smoke" by J. M. Barrie is a novel written in the late 19th century. The book explores the themes of smoking and the effects of tobacco on the protagonist's life, particularly through the lens of a bachelor who reflects on his past experiences and reluctance to give up smoking despite its drawbacks. The narrative introduces various characters that accompany the main character in his smoking adventures, wherein a peculiar mixture of humor and introspection flourishes. At the start of the story, the narrator shares his inner conflict regarding tobacco, reminiscing about the painful yet pleasurable moments tied to smoking. He describes his transformation from a bachelor entrenched in his smoking habits to a married man who learns to appreciate a smoke-free existence due to his wife's influence. The opening reveals the struggles and contradictions of a man caught between his fondness for his tobacco habits and the realities of a healthier lifestyle, setting a reflective tone that invites readers to contemplate their own vices and dependencies. (This is an automatically generated summary.)
Release date is 2006-07-29
Ted Garvin, David Garcia and the Online Distributed Proofreading Team
Keywords: Wit and humor, Pictorial; Smoking -- Anecdotes; Tobacco -- Anecdotes